2023
DOI: 10.1186/s12912-023-01502-7
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic responses to workplace violence among nursing professionals: a collaborative and comparative study in South Korea and Hong Kong

Soyun Hong,
Sujin Nam,
Janet Yuen Ha Wong
et al.

Abstract: Background Workplace violence has had a significant and negative psychological impact on nursing professionals worldwide. Concerted worldwide efforts to improve work environments have not yet removed nursing professionals from the threat of violence. It is highly essential to conduct comparative research in various working environments where the nurses of each country have unique experiences of workplace violence. The aim of this study was to examine the differences in the rate, associated fact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Nurses, due to their direct patient interaction, are particularly vulnerable to WPV compared to other clinical staff. 5 Shockingly, studies have highlighted that nurses so frequently endure violence that these incidents are often normalized as “part of the job.” 6 A recent systematic review has indicated that up to 87% of female nurses reported experiencing sexual harassment. 7 In Iran, a study found that 91% of nurses faced intimidation and bullying at their workplace, 8 while in China, 79% of nurses were exposed to different forms of WPV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses, due to their direct patient interaction, are particularly vulnerable to WPV compared to other clinical staff. 5 Shockingly, studies have highlighted that nurses so frequently endure violence that these incidents are often normalized as “part of the job.” 6 A recent systematic review has indicated that up to 87% of female nurses reported experiencing sexual harassment. 7 In Iran, a study found that 91% of nurses faced intimidation and bullying at their workplace, 8 while in China, 79% of nurses were exposed to different forms of WPV.…”
Section: Introductionmentioning
confidence: 99%
“…Acts of violence in the workplace contribute to an atmosphere of fear and psychological stresss, consequently impacting the mental health of nurses. 6 , 10 A recent study has discerned that nurses who experience WPV are more likely to suffer from burnout, which in turn was associated with less job satisfaction. 11 Another study has revealed that nurses who have experienced violence are at significantly higher risk of impaired work functioning.…”
Section: Introductionmentioning
confidence: 99%